Ex-situ population of White-rumped Shama (Copsychus malabaricus): studies of density, distribution and bird keepers in Bengkulu, Sumatra - Heri Dwi Putranto; BIENG BRATA; YOSSIE YUMIATI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Putranto HD, Brata B, Yumiati Y. 2020. Ex-situ population of White-rumped Shama (Copsychus malabaricus): Studies of density, distribution and bird keepers in Bengkulu, Sumatra. Biodiversitas 21: 865-874. Purpose of this research was to estimate number of White-rumped Shama (Copsychus malabaricus) or locally known as murai batu which are kept by Bengkulu's bird keepers, analyze its population density, population distribution, and the profile of bird keepers. Researcher used field observation method by conducting interviews during June-September 2019. Respondents were determined using purposive sampling method and sampling was continued by snowball sampling method. Bird population data were analyzed by using population density formula and population distribution formula, while profile of bird keepers was analyzed descriptively. In 9 sub-districts of Bengkulu City total of 642 birds that are kept by bird keepers in ex-situ habitat, consisting of 434 males and 208 females with sex ratio approximately of 2:1. Population density was 4.23 birds per km2 (2.86 male birds/km2 and 1.37 female birds/km2). Population distribution by a Variance-Mean Ratio formula was 4.8 or VMR > 1. Furthermore, there were 79 keepers consist of 78 male bird keepers (98.7% ) and 1 female keeper (1.27%). Eleven bird keepers (13.9%) were categorized as captive breeders and 68 keepers (86.1%) were categorized as bird hobbyists. In conclusion, density population of ex-situ White-rumped Shama in Bengkulu City was 4.23 birds per km2, and population distribution interpreted as negative binomial distribution. Bird keepers were divided into two groups, captive breeders and bird hobbyists.